Nigeria : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Nigeria. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that the Nigerian economy is exiting recession but remains vulnerable. New foreign exchange measures, rising oil prices, attractive yields on government securities, and a tighter monetary policy have contributed to better foreign exchange availability, increased reserves to a four-year high, and contained inflationary pressures. Economic growth reached 0.8 percent in 2017, driven mainly by recovering oil production. Inflation declined to 15.4 percent year-over-year by end-December, from 18.5 percent at end-2016. Higher oil prices are supporting the near-term projections, but medium-term projections indicate that growth would remain relatively flat, with continuing declines in per capita real GDP under unchanged policies.